2021
DOI: 10.1371/journal.pone.0244123
|View full text |Cite
|
Sign up to set email alerts
|

The role of aquaporin-4 in optic nerve head astrocytes in experimental glaucoma

Abstract: Purpose To study aquaporin channel expression in astrocytes of the mouse optic nerve (ON) and the response to IOP elevation in mice lacking aquaporin 4 (AQP4 null). Methods C57BL/6 (B6) and AQP4 null mice were exposed to bead-induced IOP elevation for 3 days (3D-IOP), 1 and 6 weeks. Mouse ocular tissue sections were immunolabeled against aquaporins 1(AQP1), 4(AQP4), and 9(AQP9). Ocular tissue was imaged to identify normal AQP distribution, ON changes, and axon loss after IOP elevation. Ultrastructure examina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 60 publications
3
13
0
Order By: Relevance
“…Our results reported here showing the lack of significant expression of AQP4 in the lamina cribrosa of human and porcine eyes is consistent with our previous findings with mise and rats and suggests the more universal finding, that these channels are likely not present in the equivalent of the lamina cribrosa in any mammalian eye. The minimal presence of AQP4 at the large animal lamina and the unmyelinated nerve of rodent eyes is highly evolutionarily conserved and therefore may be either advantageous for normal ONH function, and/or a protective influence for retinal ganglion cell axons from glaucoma damage [ 39 ]. There are several possible hypotheses for the potential benefit from this regional astrocytic characteristic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results reported here showing the lack of significant expression of AQP4 in the lamina cribrosa of human and porcine eyes is consistent with our previous findings with mise and rats and suggests the more universal finding, that these channels are likely not present in the equivalent of the lamina cribrosa in any mammalian eye. The minimal presence of AQP4 at the large animal lamina and the unmyelinated nerve of rodent eyes is highly evolutionarily conserved and therefore may be either advantageous for normal ONH function, and/or a protective influence for retinal ganglion cell axons from glaucoma damage [ 39 ]. There are several possible hypotheses for the potential benefit from this regional astrocytic characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…The inability to expand in the closed ONH compartment, could prevent astrocytes could from enhancing the axonal transport obstruction in axons known to occur in glaucoma. We showed that the myelinated optic nerve in normal mice is larger in area than in AQP4 null mice, due to a reduced astrocytic volume in the nulls [ 39 ]. Previous research showed that increased IOP leads to greater fluid movement from the vitreous cavity through the ONH [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The injection of microbeads into the anterior chamber produces IOP elevation known to cause RGC death that is maximal by 6 weeks [23] (Figure 4A, Figure S4, Table S1). Mice exposed to elevated IOP followed prior experience with bead injection [23, 24], having significant mean IOP elevation at three days, decreasing at two weeks and with minimal difference from baseline at six weeks (Figure S4, Table S1). Micro-dissected UON, MON, and retinal tissue was collected at three days (early, 3D), two weeks (middle, 2W), and six weeks (late, 6W) post-injection to characterize gene expression changes spanning the time course of this model (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%